2006
DOI: 10.1097/00054725-200606000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial antigens alone can influence intestinal barrier integrity, but live bacteria are required for initiation of intestinal inflammation and injury

Abstract: Intestinal flora plays a critical role in the initiation and perpetuation of inflammatory bowel disease. This study examined whether live fecal bacteria were necessary for the initiation of this inflammatory response or whether sterile fecal material would provoke a similar response. Three preparations of fecal material were prepared: (1) a slurry of live fecal bacteria, (2) a sterile lysate of bacterial antigens, and (3) a sterile filtrate of fecal water. Each preparation was introduced via gastric gavage int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Gut microbiota are assumed to elicit dysregulation in intestinal immune responses and hereby may become a factor in pathogenetic mechanisms of IBD [37][38][39][40][41]. Interestingly, binding sites for labeled bacteria were visualized on leukocytes in the lamina propria of IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota are assumed to elicit dysregulation in intestinal immune responses and hereby may become a factor in pathogenetic mechanisms of IBD [37][38][39][40][41]. Interestingly, binding sites for labeled bacteria were visualized on leukocytes in the lamina propria of IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal mucosa barriers include mechanical barrier, chemical barrier, immunologic barrier and biology barrier [18][19][20][21] , any damage of these barriers will damage intestinal mucosa barrier function. In this study, we used plasma D-xylose, endotoxin and intestine mucus sIgA to evaluate the intestinal mucosa barrier function in rats with NASH and to observe its change in NASH rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have recently demonstrated that bacterial antigens alone are able to affect the epithelial integrity; however, live bacteria are necessary to cause a sustained inflammation. 22 In this experiment we first established a dose at which indomethacin disrupts the intestinal epithelial barrier integrity in the absence of an intestinal or systemic inflammatory response. We then used this dose of indomethacin to investigate the effects of epithelial barrier disruption and increased permeability on IBD-prone axenic mice monoassociated with a single nondisease-causing bacteria.…”
Section: Discussionmentioning
confidence: 99%